Respuesta :
Answer:
b = - 21
Step-by-step explanation:
calculate m using the gradient formula
m = ( y₂ - y₁ ) / ( x₂ - x₁ )
with (x₁, y₁ ) = (- 4, - 5) and (x₂, y₂ ) = (- 6, 3)
m = [tex]\frac{3+5}{-6+4}[/tex] = [tex]\frac{8}{-2}[/tex] = - 4
y = - 4x + b ← is the partial equation
to find b substitute either of the 2 given points into the partial equation
using (- 4, - 5 ), then
- 5 = 16 + b ⇒ b = - 5 - 16 = - 21
Answer: -21
Step-by-step explanation:
We know that the equation of a line passing through points (a,b) and (c,d) is given by :-
[tex](y-b)=\dfrac{d-b}{c-a}(x-a)[/tex]
Then , the equation of a line passing through points J(-4, -5) and K(-6, 3) is given by :-
[tex](y-(-5))=\dfrac{3-(-5)}{-6-(-4)}(x-(-4))\\\\\Rightarrow\ (y+5)=\dfrac{8}{-2}(x+4)\\\\\Rightarrow\ y+5=-4(x+4))\\\\\Rightarrow\ y+5=-4x-16\\\\\Rightarrow\ y=-4x-21[/tex]
Comparing to the general intercept form of equation [tex]y = mx + b[/tex], we get
The value of [tex]b=-21[/tex]